Stop flailing: The impact of bicortically displaced rib fractures on pulmonary outcomes in patients with chest trauma — an American Association for the Surgery of Trauma multi-institutional study. Issue 4 (October 2020) - Senekjian, Lara; Birkas, Yekaterina; Buhavac, Milos; Dayal, Saraswati; Mukherjee, Kaushik; Nygaard, Rachel; Pierce, Sean; Buaza, Graciella; Sperry, Jason; Eriksson, Evert; Leon, Stuart M.; Kopelman, Tammy; et al.
Abstract : BACKGROUND: Current evaluation of rib fractures focuses almost exclusively on flail chest with little attention on bicortically displaced fractures. Chest trauma that is severe enough to cause fractures leads to worse outcomes. An association between bicortically displaced rib fractures and pulmonary outcomes would potentially change patient care in the setting of trauma. We tested the hypothesis that bicortically displaced fractures were an important clinical marker for pulmonary outcomes in patients with nonflail rib fractures. METHODS: This nine-center American Association for the Surgery of Trauma multi-institutional study analyzed adults with two or more rib fractures. Admission computerized tomography scans were independently reviewed. The location, degree of rib fractures, and pulmonary contusions were categorized. Univariate and multivariate logistic regression analyses were performed to identify independent predictors of pneumonia, acute respiratory distress syndrome (ARDS), and tracheostomy. Analyses were performed in nonflail patients and also while controlling for flail chest to determine if bicortically displaced fractures were independently associated with outcomes. RESULTS: Of the 1, 110 patients, 103 (9.3%) developed pneumonia, 78 (7.0%) required tracheostomy, and 30 (2.7%) developed ARDS. Bicortically displaced fractures were present in 277 (25%) of patients and in 206 (20.3%) of patients without flail chest. After adjusting for patient demographics, injury, and admission physiology, negative pulmonary outcomes occurred over twice as frequently in those with bicortically displaced fractures without flail chest (n = 206) when compared with those without bicortically displaced fractures—pneumonia (odds ratio [OR], 2.0; 95% confidence interval [CI], 1.1–3.6), ARDS (OR, 2.6; 95% CI, 1.0–6.8), and tracheostomy (OR, 2.7; 95% CI, 1.4–5.2). When adjusting for the presence of flail chest, bicortically displaced fractures remained an independent predictor of pneumonia, tracheostomy, and ARDS. CONCLUSION: Patients with bicortically displaced rib fractures are more likely to develop pneumonia, ARDS, and need for tracheostomy even when controlling for flail chest. Future studies should investigate the utility of flail chest management algorithms in patients with bicortically displaced fractures. LEVEL OF EVIDENCE: Prognostic and epidemiological study, level III.